Effects of the flow diversion technique on nucleotide levels in intra-cranial aneurysms: A feasibility study providing new research perspectives - Eker, Omer F.; Lubicz, Boris; Cortese, Melissa; Delporte, Cedric; Berhouma, Moncef; Chopard, Bastien; Costalat, Vincent; Bonafé, Alain; Alix-Panabières, Catherine; Van Anwterpen, Pierre; Zouaoui Boudjeltia, Karim (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The flow diverter stent (FDS) has become a first line treatment for numerous intracranial aneurysms by promoting aneurysm thrombosis. However, the biological phenomena underlying its efficacy remains unknown. We propose a method to collect in situ blood samples to explore the flow diversion effect within the aneurysm sac. In this feasibility study, we assessed the plasma levels of nucleotides within the aneurysm sac before and after flow diversion treatment. Materials and Methods: Fourteen patients with unruptured intracranial aneurysms selected for FDS implantation were prospectively recruited from February 2015 to November 2015. Two catheters dedicated to 1) flow diverter stent deployment and 2) the aneurysm sac were used to collect blood samples within the parent artery (P1), and the aneurysm sac before (P2) and after (P3) flow diversion treatment. The plasma levels of adenosine monophosphate (AMP), adenosine diphosphate (ADP) and adenosine triphosphate (ATP) at each collection point were quantified with liquid chromatography and tandem mass spectrometry. Results: The aneurysms were extradural in nine (64.3%) patients and intradural in five (35.7%) patients. They presented an average diameter of 15.5±7.1 mm, height of 15.8±4.6 mm and volume of 2549±2794 mL. In all patients (100%), 16 FDS implantations and 42 in situ blood collections were performed successfully without any complications associated with the procedure. The ATP, ADP and AMP concentrations within the aneurysm sac decreased after flow diversion (p = 0.005, p = 0.03 and p = 0.12, respectively). Only the ATP levels within the aneurysm sac after flow diversion significantly correlated with aneurysm volume (adjusted R2 = 0.43; p = 0.01). Conclusions: In situ blood collection within unruptured intracranial aneurysms during a flow diversion procedure is feasible and safe. Our results suggest that flow diversion technique is associated with changes in the nucleotide plasma levels within the aneurysm sac.